The millipede genus Epanerchodus Attems, 1901 in the Korean Peninsula, with a description of a new species (Diplopoda, Polydesmida, Polydesmidae). Zootaxa, 1350, 45–53. (Erratum) - Mikhaljova, E. V.; Lim, K.-Y. (Zootaxa, 2006)
Erratum